The invertebrates of Edgeöya, Svalbard - Coulson, Stephen (University1, 2019)
Inventory of invertebrates from two sampling visits to Edgeöya, Svalbard, in 2009 and 2010.

Species list from two field trips to Edgeöya, Svalbard.
The list comprises all species identified from soil samples collected from six locations around the coastline of Edgeöya.
The data is fully described in Ávila-Jiménez et al. (2019) The invertebrate fauna of Edgeøya, Svalbard: Arctic landscape community composition reflects pan-Arctic biogeography patterns Polar Biology https://doi.org/10.1007/s00300-019-02471-x

Inventering av evertebrater (ryggradslösa djur) från Edgeöya, Svalbard, 2009-2010.

Artlista från två fältbesök till Edgeöya.
Listan omfattar alla arter som identifierats från markprover insamlade från sex platser runt Edgeöyas kust.
Utförligare beskrivning finns i Ávila-Jiménez et al. (2019).
Evertebrater från Edgeöya, Svalbard
Keywords: ARCTIC TUNDRA; ANIMALS/INVERTEBRATES; Bio-geographical regions; Biogeografiska regioner; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Biota; Biologi och ekologi